Facial high-pressure injection injury with air in a child - S. A. Simonis; D. H. de Lange (International Journal of Emergency Medicine)
Abstract Background High-pressure injection injuries are rare injuries and are frequently underestimated due to the limited external damage. Because of their association with occupational activities, these injuries are predominantly seen in hands. Facial involvement in such traumas is extremely rare. The difference in facial anatomy compared to the extremities demands careful consideration of both associated complications and treatment options. Case A 6-year-old girl with no significant medical history was presented to the Emergency Department with a high-pressure injection injury to her right eye with a high-pressure cleaner. This resulted in injection of air at a pressure of 8 bar into the eye. She developed significant subcutaneous emphysema in the facial and neck regions. Additionally, intraorbital and intracranial emphysema were identified without any fractures. Treatment consisted of inpatient observation and antibiotic treatment. The patient was discharged after one day of observation for continued antibiotic treatment at home. Two weeks later, the patient had no residual symptoms and there were no signs of secondary infection. Conclusion High-pressure injection injuries to the face are rare and demand a different approach compared to the most common high-pressure injection injuries to the extremities. The nature of the injected material is paramount in choosing the appropriate treatment. This case illustrates that a high-pressure injection injury with air in the facial region, leading to extensive emphysema, can be managed conservatively with antibiotic therapy and inpatient observation.